Zero-current switching for the alternate arm converter through on-load tap changers - Wickramasinghe, Harith R. (2020)
The combined operation of the two arms of an alternate arm converter (AAC) phase-leg is essential for SM capacitor energy balancing but is limited to a small overlap period. The director switches (DSs) operate alternatively and the overlapping operation of the DSs provides the overlap period. The alternate operation of the two arms leads to arm inductor current interruptions increasing voltage stresses across DSs during normal operation. This paper proposes a coordinated operation of the AAC operating point and transformer on-load tap changers (OLTCs) based on power reference set-points in order to achieve ZCS of the DSs regardless of the AAC operating mode. The coordinated operation utilizes the tap positions of the converter transformer effectively and extends the operating range that offers ZCS of the DSs without additional efforts of circulating current control. Results from an AAC-based HVDC converter model derived from the CIGRE benchmark MMC system demonstrate the effective use of the transformer OLTC to achieve ZCS of the DSs in AACs.